Conceptual Metaphors of “Soul” in the New Testament of the Protestant Christian Bible - Mingcharoenwong, Patamaporn; Kaewjungate, Wuttinun (Thammasat Journal, 2026)
This research aimed to analyze metaphorical expressions that reflected conceptual metaphors of “Soul” in the Bible’s New Testament. The study employed the conceptual metaphor theory of Lakoff and Johnson (1980), Gibbs (1994), and Kövecses (2002). Data were collected from metaphorical expressions of “Soul” found in the Bible’s New Testament using a bilingual Thai-English version, the Amata Tham Contemporary Bible, which contained 511 pages and 315 scriptural passages. The findings revealed four conceptual metaphors related to “Soul” in the New Testament as follows: 1) [Soul is something possessed by humans], 2) [Soul is a person in need of protection], which included two sub-metaphors: [Soul is a person who depends on God] and [Soul is a person facing adversity], 3) [Soul is an object or a valuable entity], and 4) [Soul is an offering/worship to God]. The research findings shed light on the conceptualizations and belief perspectives regarding spirituality in the Bible, making them more explicit and concrete. In addition, metaphors related to soul in the Bible suggested that the only path for humans to enter heaven was through faith in God, as He redeemed and cleansed them of their sins.